The Use Of Nusantara Character Design In Kaela Kovalskia's Youtube Account - Setiawan, Muhammad Naufal Aldi; Fikri, M. Andi (Universitas Muhammadiyah Sidoarjo, 2024)
This research aims to examine the use of Nusantara skin character design in YouTube content, particularly on the Kaela Kovalskia account, by utilizing Roland Barthes' theory. Through a qualitative approach and data collection methods, this research utilizes content analysis, with primary data collected through documentation and secondary data gathered through literature review. The research results indicate that this study focuses on visual markers such as rattan bracelets from Papua, red fire opal stone pendants, a mix of lasem batik and sekar jati fabrics, traditional Dayak woven cloth, as well as the hammer accessories worn by the character Kaela Kovalskia. This research found that the use of those markers not only has aesthetic value but also refers to Barthes' concepts of denotation and connotation. The use of visual markers such as rattan bracelets from Papua, red fire opal stone pendants, batik fabric mixed with lasem and sekar jati, traditional Dayak woven cloth, and hammer accessories on the character Kaela Kovalskia reflects the amalgamation of rich Nusantara cultural symbols. This not only creates a strong image but also communicates a distinctive cultural identity with the aim of enhancing a sense of patriotism among the younger generation through new media such as YouTube